Modified Mineral Trioxide Aggregate—A Versatile Dental Material: An Insight on Applications and Newer Advancements - Pushpalatha, C.; Dhareshwar, Vismaya; Sowmya, S. V.; Augustine, Dominic; Vinothkumar, Thilla Sekar; Renugalakshmi, Apathsakayan; Shaiban, Amal; Kakti, Ateet; Bhandi, Shilpa H.; Dubey, Alok; Rai, Amulya V.; Patil, Shankargouda (Frontiers in Bioengineering and Biotechnology, 2022)
MTA (Mineral Trioxide Aggregate) is a material of revolution in the field of dentistry since its introduction in 1990’s. During the last ten years, the MTA has established a place in the area of dentistry, where it is highly suitable for conservative and endodontic treatments, respectively. MTA offers a wide range of fascinating clinical applications since it has a wide range of characteristics that are required for an optimal dental material. It is being extensively used for perforation repairs, apexification, root end filling (REF) material, obturation, tooth fracture repair, regenerative procedures, apexogenesis, pulpotomies (PP) and as a pulp capping (PC) because of its desired features such as biocompatibility, bioactivity, hydrophilicity, sealing ability, and low solubility. Even though its application is wide it has its own drawback that prevent it from reaching its full potential as a comprehensive replacement material, including a long setting time, discoloration, a mud-like consistency, and poor handling characteristics. MTA is a material of research interest currently and many ongoing studies are still under process. In this review the newer advancement of this versatile material by modification of its physical, chemical and biological properties such as change in its setting time, addressing the discoloration issue, inclusion of antimicrobial property, improved strength, regenerative ability and biocompatibility will be discussed. Modifications to MTA and items with different compositions but comparable applications are addressed to assist dentist in picking the proper material for fixing difficult instances with maximum competence in evidence-based practice (EBP) is essential for dental practitioners. For many years to come, an MTA-based product is expected to be at the heart of good dental practice and is still considered a gold standard. Hence it is important to have knowledge on the traditional and newer advancements of MTA.